TI_GERICHTE 12.2017.158 vom 8. Mai 2019 , Compravendita immobiliare - garanzia per difetti alle parti comuni - TI Tribunale d'appello (2019)
Compravendita immobiliare - garanzia per difetti alle parti comuni